A host-derived volatile primes context-dependent foraging behavior in parasitic nematodes via a lysosome-associated neural pathway - Sheng-Yen Wu; Yan Zhao; Yuntao Yang; Fanxi Tang; Yixuan Li; Jinju Xu; Honghong Deng; Youming Hou (Proceedings of the National Academy of Sciences, 2026)
Entomopathogenic nematodes (EPNs) are valued for sustainable pest control, yet their efficacy hinges on matching foraging behavior to host ecology. The nematode Steinernema carpocapsae , long regarded as an ambusher, paradoxically infects the cryptic red palm weevil ( Rhynchophorus ferrugineus ), which resides deep in plant tissue. Here, we show that this contradiction stems from a context-dependent modulation of foraging-related behaviors, triggered by butylated hydroxytoluene (BHT)—a host-derived volatile emitted by R. ferrugineus larvae. BHT functions as a potent behaviorally active volatile, increasing locomotion, jumping, host attraction, and infection success in S. carpocapsae . Mechanistically, BHT engages a lysosome-associated signaling pathway involving mfsd8 , SLC17A5 , and ptr . Knockdown of these genes disrupted BHT-induced behavioral changes, supporting their functional involvement. Our findings extend existing context-dependent models of nematode foraging by providing mechanistic insight into chemically induced behavioral modulation. This work opens possibilities for improving EPN biocontrol efficacy via ecological or molecular priming.